2016
DOI: 10.1139/cjpp-2015-0569
|View full text |Cite
|
Sign up to set email alerts
|

Relative risk for cardiovascular morbidity in hemodialysis patients regarding gene polymorphism for IL-10, IL-6, and TNF

Abstract: Uremia-related inflammation is prone to be a key factor to explain high cardiovascular morbidity in hemodialysis patients. Genetic susceptibility may be of importance, including IL-10, IL-6, and TNF. The aim was to analyze IL-10, IL-6, and TNF gene polymorphisms in a group of hemodialysis patients and to correlate the findings with cardiovascular morbidity. This study included 169 patients on regular hemodialysis at Zvezdara University Medical Center. Gene polymorphisms for IL-10, IL-6 and TNF were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In our study, the CC genotype was correlated with associated hypertension, while in the study by Tosic-Dragovic et al [ 32 ] patients with G allele of the IL-6 gene experienced 1.5-fold higher risks for cerebrovascular accident. A meta-analysis [ 33 ] revealed that IL-6 -174 G/C polymorphism was not significantly associated with hypertension under all of the genetic models, but the authors concluded that several studies are needed especially in Europeans and Middle-Eastern populations.…”
Section: Discussionsupporting
confidence: 45%
“…In our study, the CC genotype was correlated with associated hypertension, while in the study by Tosic-Dragovic et al [ 32 ] patients with G allele of the IL-6 gene experienced 1.5-fold higher risks for cerebrovascular accident. A meta-analysis [ 33 ] revealed that IL-6 -174 G/C polymorphism was not significantly associated with hypertension under all of the genetic models, but the authors concluded that several studies are needed especially in Europeans and Middle-Eastern populations.…”
Section: Discussionsupporting
confidence: 45%
“…Different haplotypes in the IL-6 gene can determine the levels of its transcription. The IL-6 gene is located on chromosome 7p21 and has several polymorphisms in the promoter regions (-174 G/C, -634 C/G, -572 G/C and -597 G/A)17 associated with increased risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Song et al8 published that genotypes IL-6-634GG and IL-6-174CC were associated with a higher risk of cardiovascular events in HD individuals. Nonetheless, Tosic Dragovic et al,17 in addition to IL-6, also evaluated polymorphisms in IL-10 and TNF and concluded that cardiovascular morbidity could be under the influence of genetic polymorphisms in these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is limited to candidate gene association studies, which have significant issues with reproducibility and publication bias. Studies looked for SNP associations with hemodialysis outcomes including vascular access issues, 56 - 61 biochemical indices, 62 - 65 inflammation, 66 - 68 cardiovascular comorbidities 66 , 69 - 75 and mortality 76 - 79 and PD outcomes including peritoneal transport characteristics, 80 - 84 peritonitis risk, 85 - 87 or risk of encapsulating peritoneal sclerosis 88 ( Supplemental Table 1 ). Sample sizes were inadequate to confidently identify variants of reasonable effect sizes (average sample size of 246, range 67-777 patients).…”
Section: Reviewmentioning
confidence: 99%